Magnitude of malaria and associated factors among febrile adults in Siraro District Public Health facilities, West Arsi Zone, Oromia, Ethiopia 2022: a facility-based cross-sectional study - Yosef Yohanes Lakew; Anteneh Fikrie; Sisay Bedane Godana; Fatuma Wariyo; Wongelawit Seyoum (Malaria Journal, 2023)
Abstract Background Despite significant efforts made to control malaria in Ethiopia, the disease remains one of the top public health problems in the country. Baseline malaria prevalence and associated factor at high malaria area is important to guide malaria control interventions, there was paucity of information regarding the study area. Therefore, the aim of this study was to determine prevalence of malaria and associated factors among febrile adults in Siraro district health facilities, West Arsi Zone, Oromia, Ethiopia. Methods Institution-based cross-sectional study was conducted among 317 febrile adult patients at Siraro district health facilities. Structured pre-tested questionnaires were used to collect data. Epi-data version 3.1 and SPSS version 23 were used for data entry and analysis respectively. In order to identify factors associated with malaria infection bivariable and multivariable binary logistic regression analysis was employed, The Adjusted Odds Ratio (AOR) with a 95% confidence interval (CI) and p-value of < 0.05 was computed to show the strength of the association. Results The overall prevalence of malaria at the study area was 130 (41.0%) [(95% CI 35.3–46.7)]. Occupation (being farmer) [(AOR = 6.05; 95% CI 1.38, 26.49)], having poor knowledge on malaria transmission [(AOR = 2.95 95%; CI 1.48–5.88)], house with wood wall [(AOR = 2.71; 95% CI 1.34–5.49)], and number of windows (≥ 3) in the house [(AOR = 6.82; 95% CI 1.05, 44.40)] were identified to be significantly associated with magnitude of malaria in the study area. Conclusion The prevalence of malaria at the study area was high as compared with the national wide figures. Being farmer, having poor knowledge on malaria transmission, and housing condition (house with wood wall and houses with three and above windows) were found to be significantly associated with malaria infection in the study area. Therefore, there has to be an emphasis on addressing the factors by providing sustainable health education for the communities to improve their housing condition and knowledge of community on the way of malaria prevention.